AN ANALYSIS OF FLOUTING MAXIM IN “THE B.F.G” MOVIE - Nur Ulfah, Rena Al Asyifa; Afrilia, Resti (PROJECT (Professional Journal of English Education), 2018)
This research studies about flouting maxim in The B.F.G movie. The research concerns on finding the flouting maxims in The B.F.G movie. This research employed mainly descriptive qualitative method to support in interpreting and analysing the data. The data of this research were utterances produced by Sophie and BFG as main characters in The B.F.G movie. The context of the research was the dialogues of the movie. The data sources of this research were The B.F.G and its script. Meanwhile, the primary instrument of this research was the researcher ourselves. The data were collected by downloading the movie and the script, watching the movie, and then collecting the data which reflects the phenomena of maxim flouting. The paper examines the use of flouts in different situations and explores in what situations the different characters flout the maxims for any conversation. The results show that there were 10 flouting maxims of quantity (42%); 10 flouting maxims of relevance (42%); 2 flouting maxims of quality (8%); and 2 flouting maxims of manner (8%). Hence the total number of flouting maxims is 24. These results suggest that the use of flouts has to do with their different personalities and communities.Keywords: Cooperative Principle, Grice’s Maxim, Flouting MaximHow to Cite: Ulfah-1, R.A.A.N.U.-1., Afrilia, R-2. (2018). An Analysis of Fluting Maxim in BFG Movie. Project, X (X), XX-XX. INTRODUCTIONCommunication is a medium to convey meaning from one to another. As stated by Yule (2006) that communication involves word recognition and meaning recognition. There could be hidden intention in some utterances. Failing to recognize those intentions may lead to misunderstanding and even a dispute. Nevertheless, listener is not always to be in guilt. Sometimes in communication, the speaker may provide incomplete or unclear utterance hence the listener found difficulties to comprehend. Thus it is claimed that language as a tool for communication serves as an instrument to maintain a good relationship between the speaker and the hearer. Dealing with language and communication, cooperative principle proposed by Grice serves as means to achieve effective communication. It is described that speakers and listeners must give contribution as required by each other so that both of them may come to the same understanding of the meaning they are trying to convey. Grice elaborates four conversational maxims: maxim of relevance, maxim of quantity, maxim of quality, and maxim of manner. During conversation, speakers may break the rule of the maxims. The flouting of the maxims may occur in daily life or in movies. Movies as one of literary works mostly functions to entertain the audience. The flouting maxims in movies may be intentionally created to achieve the purpose of entertaining. The BFG is one fantasy adventure film released in 2016 by Walt Disney. It tells about the journey of two different species, a human (Sophie) and a giant (that Sophie called Big Friendly Giant). Since they are from different group of communities, their communication may run ineffective. This study aims at analyzing the flouting maxims occurred in The BFG movie.The Cooperative Principle Cooperative Principle is the basic principle in pragmatics. The Cooperative Principle is principle of conversation that was proposed by Grice. He called The Cooperative Principle as when we try to talk to be cooperative by elevating. He says, “make your conversational contribution such as is required, at the stage at which it occurs, by the accepted purpose or direction of talk exchange in which you are engaged.” Within this principle, he intended four maxims.(Grundy, 1998) (in Ginarsih, 2014)Grice’s MaximMaxim of RelevanceMaxim of relation: This maxim may seem clear in the first look but as Grice himself mentioned it is very difficult to define it exactly: "Though the maxim itself is terse, its formulation conceals a number of problems that exercise me a good deal: questions about what different kinds and focuses of relevance there may be, how these shift in the course of a talk exchange, how to allow for the fact that subjects of conversations are legitimately changed, and so on. I find the treatment of such questions exceedingly difficult, and I hope to revert to them in later work." Grice ( in Kheirabadi, 2012).Maxim of Quantity Maxim of quantity requires that participants of a conversation give their contribution as is required in terms of the quantity of information. To say beyond the quantity of information needed in the conversation is to break the maxim. In making their contribution to the conventional talk, participants should gauge the amount information that is really sought for and give it as much as is necessary. They should not make their contribution either more informative or less informative. (Seken, n.d.2015)Maxim of QualityMaxim of quality requires conventional participants to say things that are true or things that they believe to be true. That is, they do not say anything than they believe to be false or anything of which they do not have any evidence. In other words, to comply with this maxim, a speaker in a conventional exchange must speak on the basis of facts, or he/she must have factual evidence by which to sufficiently support what he/she says as truth. (Seken, n.d.2015)Maxim of Manner Utterances may conform to the maxims or may disobey them by infringing, opting out, and flouting or violating. The infringement of the maxims is because of the speaker‟s imperfect knowledge of linguistic. When speakers decided to be uncooperative, they opt out of observing the maxims. ( Thomas 1995 in Jafari, 2013) Maxim Flouting Flouting a maxim is the case when a speaker purposefully disobeys a maxim at the level of what is said with the deliberate intention of generating an implicature. In this case, the speaker’s choice not to observe the maxim by the words he/she utters may be related to the some motive (such as politeness, style of speaking, etc.) (Seken, n.d.2015).According to Thomas (1995:64 in Mohammed & Alduais, 2012) flouting a maxim occurs where a participant in a conversation chooses to ignore one or more of the maxims by using a conversational implicature. Ignoring maxims by using conversational implicatures means that the participant adds meaning to the literal meaning of the utterance. He further explains the conversational implicature that is added when flouting is not intended to deceive the recipient of the conversation, but the purpose is to make the recipient look for other meaning. Moreover Black (2006:25 in Mohammed & Alduais, 2012) explains that a speaker who flouts maxims is actually aware of the Cooperative Principles and the maxims. In other words, it is not only about the maxims that are broken down but that the speaker chooses an indirect way to achieve the cooperation of the communication.Types of Flouting Maxim In ( Grice’s theory in Nur & Fatmawati, 2015) there are four types of maxim flouting. They are quantity maxim flouting, quality maxim flouting, relevance maxim flouting, and manner maxim flouting. Quantity Maxim FloutingWhen a speaker flouts the maxims under the category of Quantity, she/he blatantly gives either more or less information than the situation demands.For example: A : The other giants. Are they nice, like you a nice?B : No, I regret to say that the guys would eat you alive bite. My twenty four foot, but not in Giant country, and that's where you are. In Giants country now.In the example above, it is not appropriate, because when A asks the B about another giant, B does not answer according to the question. He give more information that not needed by A.Quality Maxim Flouting Thomas (in Fami 2015:15) said that flout maxim of quality occur when the speaker say something which is blatantly untrue or for which he/she lack adequate evidence.For example:A : Not as it happens to me, it is most terrible speakB : Well, I think you speak beautifullyIn the example above, B say untrue or lie. She do this, because she doesn’t want B sad with his speaking.Relevance Maxim FloutingFlouting of maxim relevance, (Ginarsih 2014, n.d.) said that by changing the subject or by failing the address the topic directly is encountered very frequently. For example:A : You mean of my life. For the rest of my life?B : Hey, do not you cold?In this case B did not answer according to the question, B changes the topic of conversation. Manner Maxim FloutingAccording to (Ginarsih 2014, n.d.) The maxim under the category of manner is exploited by giving ambiguity and obscure expressions, failure to be brief and orderly. It is often trying to exclude a third party, as in this sort of exchange between husband and wife.A : Where are you off to?B : I was thinking of going out to get some of that funny white stuff for somebody.A : OK, but don’t be long – dinner is nearly readyB speaks in an ambiguous way, saying “that funny white stuff” and“somebody”, because he is avoiding saying “ice cream” and “her/his Daugther”, so that his little daughter does not become excited and ask for the ice cream before her meal. Sometimes the speakers play with words to heighten the ambiguity, in order to make a point.Movie(Chandra Yuliasman 2014) Movie is happen based on script, but it reflect to our daily life activity mostly. That is why the researcher interested to use movie as media to increase the researcher understanding about flouting maxim. Movie also affect masses in childhood and youth. Movie is also called a film or motion picture, is a series of still or moving images. Based on the theories above, the researcher chose “The BFG (Big Friendly Giant)” as the object of the research.The B.F.GThe B.F.G is a 2016 American fantasy adventure film directed and produced by Steven Spielberg, written by Melissa Mathison and based on the 1982 novel of the same name by Roald Dahl. In the film, an orphan human girl be friends a benevolent giant, dubbed the "Big Friendly Giant", who takes her to Giant Country, where they attempt to stop the man-eating giants that are invading the human world. The writers chose The B.F.G, because in the film contain about friendship and courage, in that movie also have morality and ethics quotes. Steven Spielberg is known for his quality films, such as Jurrasic Park. He has also received three Oscars, and received a Life Achievement Award from the American Film Institute (AFI). Steven hooked some Hollywood actresses to play in the movie B.F.G, such as: Mark Rylance (B.F.G), Ruby Barnhill (Sophie), Penelope Wilton, Jemani Clement, Rebecca Hall, Rafe Spall, and Bill Hader. Steven Spielberg films this In the premiere of premiere The BFG managed to triumph in the Top 10 Box Office by collecting revenues of USD 31 million. Although not a chance to taste the top of the Box Office but The BFG still loved by his fans, especially for lovers of fantasy and adventure movies.METHODThis research uses a descriptive qualitative method to analyse the flouting maxim in The B.F.G movie directed by Steven Spielberg. According to Holloway (in Nur & Fatmawati, n.d.) qualitative research is a form of social inquiry focusing on the interpretation of experience and the world by people.” Therefore, this research is conducted systematically through the technique of data collecting and data analysis. The data are taken from the script, the writers analysed of flouting maxim of quantity, maxim of quality, maxim of relation, and maxim of manner based on Grice’s theories, being used to choose the most frequently method among them, the writer used percentage category based on Multihajz’s formula, in Selvia (2014) as follows:  P = Percentage F = Frequency n = Number of Maxims RESULTS AND DISCUSSIONResultsThere are 24 conversations from 100 conversations that found in The B.F.G Movie between the main characters, Sophie and B.F.G that flouted the Grice’s cooperative principle. They flouted the maxim of quantity, the maxim of quality, the maxim of relation, and the maxim of manner. In the calculation the writers employed percentage technique as described below:Table 1The Classification of Maxim:NoTypes of MaximQuantityPercentage1.The Maxim of Quantity1042 %2. The Maxim of Quality28 %3The Maxim of Relevance1042 %4The Maxim of Manner28 %Total24100 %From the classification above, it could be seen clearly that among four types of maxim in conversation between the main characters, Sophie and B.F.G in “The B.F.G” Movie, the maxim of Quantity and Relevance were the most identifiable types. First is Quantity. There are 10 conversations or cover 42 %. The second was the maxim of Relevance; there are 10 conversations or cover 42 %. The third was maxim of Quality; there are 2 conversations or cover 8 %. The fourth was the maxim of Manner; there are 2 conversations or cover 8 %. Based on the table above, here are the explanations of each maxim that the main character, Sophie and B.F.G flouted in The B.F.G Movie. The maxim of quantitySophie : The other giants. Are they nice, like you a nice?B.F.G : No, I regret to say that the guys would eat you alive bite. My twenty four foot, but not in Giant country, and that's where you are. In Giants country now.Analysis: It is not appropriate, because when Sophie asks the BFG about another giant, the BFG does not answer according to the question. He give more information that not needed by Sophie.Sophie : We can’t have secrets. I'll tell you mine. I sneak around at night too, and that still sometimes theft and lying. So I’m alone at the time. I've never had a best friend, I told you all thatB.F.G : We got over.Analysis: The BFG did not give the right reasons to reply to a statement from Sophie.Sophie : You should not let them treat you like that. You should notB.F.G : Live with nine giant eats beans. They take so I return. Murmur good dreams. It's what I can do, I do something. I do something.Analysis: The BFG ignored Sophie’s suggestion of another giant treating the BFG badly and he changed the subject.Sophie : No I’m not.B.F.G : Yes you here. If you are a human being and human being is a strawberry cream for giants. They are the prey of those giants out there, so you stay in a nice safe place right here. Analysis: BFG answer does not fit with the context of the conversation at that time.B.F.G : Someone called me a big, friendly giant. How should I call you? Sophie : My name is SophieAnalysis: Sophie does not understand about a nickname, so she just answers with her name only "Sophie".B.F.G: So you're an orphan?Sophie: Yes. You took me to an orphanage. You did not know?Analysis: Sophie did not give the right reasons to reply to a statement from B.F.G.B.F.G: I did not know that. Are you happy there?Sophie: No! I hate that. The lady who runs it is incompetent and she’s crazy rules and you get punish a lot.Analysis: In this conversation, Sophie should answer yes or no , because the question is are you happy there ?.Sophie : Being is not be ing .What is that green thing ?B.F.G : Frobscuttel. All giant drink frobscottel.Analysis: BFG answer does not fit with the context of the conversation at that time.Sophie : Where are you going now ?B.F.G : A dreams blow .It's what I do next.Analysis: BFG answer does not fit with the context of the conversation at that time. In this conversation Sophie asks where, it means that ask about place.Sophie : But why did you bring me here? Why did you take me?B.F.G : I had did to take you, because the first thing you, you would do spread the news you actually saw a giant and then there would be a big fuss and all human beans would be looking for the giant dresses all excited, and then I would be locked up in a cage to look at me with all the noisy hypo-fat and crocodiles and giraffes. And then there would be a huge hunt for all the boy giantsAnalysis: The BFG gives too much give reason to Sophie, should the BFG give Sophie a simple and precise reason for the question.The maxim of RelevanceSophie : Then, who are you? What kind of monster are you?B.F.G : You as me wrongAnalysis: BFG does not honestly reply to Shopie that he is a giant kind.Sophie : You mean of my life. For the rest of my life. B.F.G : Hey, do not you cold?Analysis: BFG did not answer according to the questionSophie : What did you work? B.F.G : And now she asks me to tell you very big secrets.Analysis: BFG did not answer according to the questionSophie : Flesh head ,he comes to eat me, my blood will be on your hands. B.F.G : Everything about you going against my better judgment.Analysis: BFG tries to make Shopie calm by diverting the conversationSophie : Look at all the stars! B.F.G : Often when it is clear I hear distant music living of the stars in the skyAnalysis: When Shopie wants to show something, BFG answer it with things that are not appropriate.Sophie: Really? B.F.G : You think I'm kidding, right? Analysis: BFG should simply answer "yes" or "no".Sophie : Are there bad dreams here too? B.F.G : It will a TrogglehumperAnalysis: BFG did not answer the question correctly.Sophie : Make them all happy. BFG, your father and your mother taught you about dreams? B.F.G : The Giants do not have mothers or fathers. Analysis: BFG should simply answer “has” or “has not”.Sophie : What is the Sophie’s dream? B.F.G : A golden Phizzwizard. I had not seen in a while. Analysis: BFG does not explain what dreams Sophie will experience.Sophie : You snapped me.B..F.G : Well, you are right. After all, you're just a little thing. I can’t help thinking what your poor mother and father must be …Analysis: BFG should simply answer "yes" and "no", and not discuss the unnecessaryThe maxim of QualityB.F.G : You do, you really do?Sophie : Simply beautifully.Analysis: In this situation of conversation, Sophie gives untrue respond to B.F.G or she lies, because she didn’t want make B.F.G sad with B.F.G’s sentence.B.F.G : Not as it happens to me, it is most terrible speak.Sophie : Well, I think you speak beautifully.Analysis: In this conversation, Sophie say untrue or lie. She did it, because she didn’t want B.F.G sad with his statement.The maxim of mannerSophie : Blood bottler ? B.F.G : Yes and butcherSophie : The butcher. Please don’t eat me.Analysis: BFG does not explain in detail about Bottler.Sophie : But then I wake up.B.F.G : And you wake up.Sophie : But not here.Analysis: There is no alignment in the conversationDiscussionThe writer found total numbers of flouting maxim that produce by main character in “The B.F.G” movie those were 24 utterances. Then divided into four types of flouting, they were quality which had 10 data or 42%, quantity had 2 data or 8%, relevance had 10 data or 42% and manner had 2 data or 8%. Thus the most frequent category of flouting maxim produce is the main character was maxim of quality and maxim of relevance. It means that in this movie, The BFG tended to conduct his flouted utterance for move the conversations. CONCLUSIONThe aim of this research is to find out the flouting maxim by the main characters in “The B.F.G” movie. The result show the most frequent category of flouting maxim by the main character was quality and relevance. It indicates that based on the maxim of quantity, there are some conversations that giving more or less information. Based on the semantics theory it is wrong, because giving more information than the need is flouting the maxim of quantity. For the maxim of relevance, there are some conversations that are not relevance, it is related with Ginarsih statement relevance maxim flouting by changing the subject or by failing the address the topic directly is encountered very frequently. There are only two flouting maxims of quality and manner was less frequent. It indicates mostly the conversation in The B.F.G movie is cooperative. It is different with the previous study, from Iniyanti, A et.al (2014) they found two flouting maxims, there are: maxim of relation and maxim of manner. And from Al-Qaderi (2015) he found that the maxim of quantity was most frequently flouted.After the research, the researcher took a conclusion that even the famous movie, the flouting maxims are can’t be avoid. ACKNOWLEDGMENTSPlace Acknowledgments, including information on the source of any financial support received for the work being published. Place Acknowledgments, including information on the source of any financial support received for the work being published.